The role of higher education institutions : recruitment of elites and economic growth - Elise S. Brezis; François Crouzet (Center for Economic Studies and ifo Institute (CESifo), 2004)
The aim of this paper is to examine the evolution of recruitment of elites and to investigate the nature of the links between recruitment of elites and economic growth. The main change that occurred in the way the Western world trained its elites is that meritocracy became the basis for their recruitment. Although meritocratic selection should result in the best being chosen, we show that meritocratic recruitment actually leads to class stratification and autorecruitment. We analyze the consequences of stratification resulting from meritocratic selection for the development of a country, and show that these consequences are dependent upon the type of technological changes occurring in the country.
Keywords: O15; O40; I21; 330; economic growth; education; elites; meritocracy; recruitment; social mobility; stratification; Wachstumstheorie; Humankapital; Elite; Sozialstruktur; Bildungswesen; Theorie